UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAN SUBFRAKSI DAUN PEPAYA (CARICA PAPAYA L.) TERHADAP BAKTERI PENYEBAB JERAWAT - Rika Hartati (Acta Pharmaceutica Indonesia, 2024)
Propionibacterium acne and Staphylococcus epidermidis are the major bacteria that infect skin which can cause many disease in the skin, one of them is acne. Papaya is one of the plants that has many activities, such as antibacterial activity. In traditional use, papaya leaves used for treatment of acne. In this study, the antibacterial activity of n-hexane, ethyl acetate, and ethanol papaya leaves extract were tested against Propionibacterium acne and Staphylococcus epidermidis ATCC 12228 using agar diffusion disc method, microdilution method to determine minimum inhibitory concentration (MIC), and bioautography test. The preliminary result with diffusion disc showed that at 5% concentration of n-hexane extract of papaya leaves produced the largest inhibit zone for both bacteria, 7,43 mm for Propionibacterium acne and 7,78 mm for Staphylococcus epidermidis. The result showed that the MIC of n-hexane extract of papaya leaf were >4096 µg/mL. The result of the bioautography test of n-hexane extract showed the inhibition zone at Rf 0,09-0,28 and Rf 0,63 in chloroform-n-hexane system (6:3) for Propionibacterium acne. Based on the test result, the n-hexane extract of papaya leaves was continued to the fractination stage by chromatotron method and the compound at Rf 0,27 were selected as the target. The fraction was monitored by thin-layer chromatography (TLC) and the fraction contained the active compound was continued to subfractination stage by preparative chromatography method. The subfraction was tested against Propionibacterium acne and Staphylococcus epidermidis by bioautography method at 600 µg/mL concentration. It resulted an inhibitory zone at Rf 0,25-0,27 for Staphylococcus epidermidis and Rf 0,27 for Propionibacterium acne. Based on the result characterization of subfraction of n-hexane extract of papaya leaves by specific visualization reagent, the subfraction was predicted contain steroid/triterpenoid compound. Keywords: antibacterial, acne, papaya leaves, Carica papaya L., biootografi